Pengaruh Consumptive Habit dan Kemudahan Transaksi Online Terhadap Business Productivity dengan Fasilitas Kemudahan IT sebagai Variable Moderasi - Virgo Simamora; Tri Wahyuningsih (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2019)
The growth of e-commerce in Indonesia makes the number of business people in e-commerce also increase. Along with this growth, it has an impact on competition among increasingly competitive e-commerce players. Although the development of e-commerce is high, Indonesian people are still afraid to make online purchasing decisions, because of the low level of consumer confidence in shopping online. This study aims to analyze the effect of consumptive habbit and ease of online transactions on business productivity with IT facilities as a facility variable moderation. with the consumptive habbit, online transactions, and the ease of IT will make a company grow and increase its productivity in accordance with technological developments. In this study using a survey. The population of this research was conducted at the University of August 17 Jakarta students. While the sample in the study This is a student who already has a job. In this study also uses Rondom Sampling, which is that any writer found can be used as a sample. Data collection can also be done by giving questions n to respondents and tested by the analysis method of validates test and SmartPLS reliability. Keyword : consumptive habit, transaksi online,kemudahan IT dan business produktifity